Examining the Effects of Nonprofit Brand Communications on Nonprofit Brand Evaluation - Apaydın, Fahri (Richtmann Publishing, 2011)
Despite the importance for the nonprofit organizations to communicate with the donors to receive support from them in thenonprofit sector, there have been surprisingly few researches examining communication and fundraising in the nonprofit sector. To receivemore support from the donors, nonprofit organizations should provide information about the needy, the organization itself, and its activitiesnot just to donors, who might be accepted as customers, but to the public in general as well. Nonprofit organizations like profitorganizations communicate with the environment mainly in two ways: controlled and uncontrolled communication. Having a strong brandalso helps nonprofit organizations to send messages to the donors. The effects of these communication tools on donors’ satisfaction, brandattitude, and giving intentions are examined in this paper. Results reveal that controlled communication and brand name play animportant role in providing information to donor and affecting their satisfaction, attitudes and behaviors.